Quantum coherence control for radio-frequency dressed cold atom systems - Foxon, Bethany (2021)
The ability to understand and control the internal state of the atom is essential to cold atom schemes. From quantum memories and fundamental physics experiments to timekeeping and inertial sensing, precise state manipulation is a key element. The use of static and AC-dressing fields can generate complex potential geometries, such as optical lattices, shell traps and toroidal shapes. However, the increased complexity of these topologies presents a number of complications which need to be addressed.